Pencirian Struktur Kota: Tinjauan Teoritik dan Pengujian Empirik - B. Kombaitan (The Institute for Research and Community Services, Institut Teknologi Bandung, 2001)
Suburbanization In development of large cities and metropolitan in Indonesia have shown the multinodal growth pattern. Peri-urban area has grown into housing job activities and service centers as it may follow the polycentric structure. This paper explores the phenomenon of the urban spatial structure development based on the theoretical framework and empirical test possibility. The theoretical background discusses the urban structure models, critics to monocentric model and polycentric development An understanding of the polycentric development can lead to the identification of an research agenda for Indonesian cities.